Antifungal Activity of Cymbopogon flexuosus Essential Oil and its Effect on Biofilm Formed by Candida parapsilosis and Candida tropicalis on Polystyrene and Polyvinyl Plastic Surfaces - Al-Ghanayem, Abdullah A. (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim: To determine the antifungal and antibiofilm activity of Cymbopogon flexuosus (Lemongrass oil) against C. parapsilosis and C. tropicalis. Materials and Methods: Lemongrass oil, was analyzed by GC-MS. Antifungal activities, minimum inhibitory concentration, and minimum fungicidal concentration against C. parapsilosis and C. tropicalis were determined. The effect of LGO inhibiting biofilm formation by these Candida species on different surfaces was evaluated. Cytotoxicity of Cymbopogon flexuosus (Lemongrass oil) on human keratinocytes (HaCaT) cells was evaluated under in-vitro conditions. Results: The major compounds found in LGO were 4-tert-butylcalix 4 arene (58.52%), diethyl 3, 4-dihydro-1-naphthalenylester (8.13%), 7,9-Di-tert-butyl-1-oxaspiro(4,5)deca-6,9-diene-2, 8-dione (8.84%) and hexadecanoic acid (4.83%). The essential oil had a considerable antifungal activity against both the Candida species. Further, a sub MIC concentration (0.5%) in the medium inhibited the biofilm formation on polystyrene and polyvinyl plastic surfaces. The in-vitro cell viability of HaCaT keratinocytes in presence of LGO was studied and the IC50 value was observed at 1250 µg/ml concentration. Conclusion: The active components of LGO with antifungal and biofilm activity can be effectively used for controlling the biofilm formation by C. parapsilosis and C. tropicalis on polystyrene and polyvinyl plastic surfaces. Further investigations on the bioactive components present in LGO may be useful to control biofilm-related infection.
Keywords: Antifungal; Antibiofilm; Candida tropicalis; Candida parapsilosis; Cymbopogon flexuosus